Design of a bioactive scaffold system for hard tissue engineering - Güngör Özkerim, Perihan Selcan (Institute of Science and Technology, 2013)
Nanofibrous double-layer matrices were prepared by electrospinning technique with the bottom layer formed from PCL (poly--caprolactone) / PLLA (poly-l-lactic acid) blend nanofibers and the upper layer from PCL/Gelatin blend nanofibers. Gelatin microspheres were incorporated physically in the middle of these two layers for controlled growth factor delivery. This sandwich system prevented microsphere leakage from the scaffold. Bead-free nanofibers with uniform morphology could be obtained by 10% w/v concentrations of PCL/PLLA and PCL/Gelatin solutions. Microspheres prepared by 500-rpm stirring rate and cross-linked with 7.5% glutaraldehyde solution were chosen after in vitro release studies. The optimized conditions were used to prepare fibroblast growth factor-2 (FGF-2) loaded microspheres. Cell culture studies with FGF-2 loaded microspheres showed that the growth factor could be actively loaded into the system and enhanced the cell attachment and proliferation. To test the effect of gelatin on cell adhesion, cell culture was performed with PCL/PLLA matrices with or without PCL/Gelatin layer. Cell attachment was significantly higher when PLLA replaced by gelatin. To investigate cell differentiation on the designed scaffold system adipose tissue derived stem cells (ADMSCs) were used and microspheres within the scaffolds were loaded with bone morphogenic protein2 (BMP-2). The effect of scaffolding on differentiation of ADMSCs towards osteogenic lineage was evaluated by various markers. According to the results, all experimental samples were biocompatible and supported the proliferation and differentiation of ADMSCs.
Sert doku mühendisliği için biyoaktif hücre iskelesi tasarımı
Thesis (Ph.D.) -- İstanbul Technical University, Institute of Science and Technology, 2013
Keywords: Biyoteknoloji; Biotechnology